2020
DOI: 10.3109/13668250.2020.1762383
|View full text |Cite
|
Sign up to set email alerts
|

Ensuring the reproductive rights of women with intellectual disability

Abstract: Background: Women with intellectual disability experience disparities in sexual and reproductive health care services. Methods: To explore perceptions of caring for persons with disability, including individuals with intellectual disability, we conducted open-ended individual interviews with 20 practising physicians and three video-based focus group interviews with an additional 22 practising physicians, which reached data saturation. Interviews were transcribed verbatim. We used conventional content analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 40 publications
0
24
0
Order By: Relevance
“…For example, recent research has emphasized the importance of training medical providers to support the reproductive rights of women with intellectual disability, an area that is also likely essential for autistic women. 92 Regarding parenting, training CPS workers holds great potential, given that CPS professionals consistently cite a desire for increased training in disabilities and that caregivers with intellectual disability are over-represented in the welfare system. 19,93 Authorship Confirmation Statement C.G.M.…”
Section: Research Recommendations and Future Directionsmentioning
confidence: 99%
“…For example, recent research has emphasized the importance of training medical providers to support the reproductive rights of women with intellectual disability, an area that is also likely essential for autistic women. 92 Regarding parenting, training CPS workers holds great potential, given that CPS professionals consistently cite a desire for increased training in disabilities and that caregivers with intellectual disability are over-represented in the welfare system. 19,93 Authorship Confirmation Statement C.G.M.…”
Section: Research Recommendations and Future Directionsmentioning
confidence: 99%
“…Increased prevalence of adverse outcomes, insufficient focus on health promotion, and lack of good health care services ( 4 ) are mostly reported in these groups ( 5 , 6 , 7 ). Although numerous laws are put in place to ensure the rights, especially the reproductive rights of IDW such as the right to equality, access to reproductive health, and the right to start a family ( 8 ), the implementation of these laws is scarce ( 9 , 10 , 11 ). Yet, other factors that prevent IDW from getting the care that they are entitled to include physical barriers for assessment, caregiver issues, access to health services, transportation difficulties, and a deficit in skilled providers ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Research [46] has also described gynecologists having di culties with shared decision making with patients with intellectual disability because of communication problems leading to physician led treatment decisions. Previous research ndings [42] also showed that not all gynecologists knew about human rights concerning sexual and reproductive health of women with intellectual disability concerning supporting and prescribing hormone depots and sterilization as routine practice [42].…”
Section: Discussionmentioning
confidence: 99%
“…The main motives were pregnancy prevention, menstrual suppression and the fear of pregnancy resulting from a sexual assault [16,41]. Current research indicates that gynecologists do not know about human rights concerning sexual and reproductive health of women with intellectual disability and that they support and prescribe hormone depots and sterilization as routine practice [42].…”
mentioning
confidence: 99%